Pendokumentasian Aplikasi Ragam Hias Budaya Betawi pada Desain Interior Ruang Publik CafÃ© Betawi - Nediari, Amarena; Hartanti, Grace (Humaniora, 2015)
Various ornaments of Indonesia come from the ethnic groups from all over the archipelago. Ornament is a tangible culture which has specific meaning and purposes. Its meaning does not change throughout the ages. Betawi culture has become cultural roots for most people in Jakarta which also as the capital city of Indonesia. Betawi culture is seen in a wide variety of dance, batik, decorative ornaments, and culinary. Betawi ornament can also be seen in the architecture and public areas since the geometrical shape is very easy to apply as interior element. The application of Betawi ornaments in a restaurant interior represents the idea of dining area in Betawi house. The study of Betawi ornaments was conducted by documentation of decorative elements in a restaurant as a public space. Objective of this research is to preserve various ornaments of Betawi culture. So that, the data can be valuable as an inspiration for designing restaurant interior with Betawi style. Generally, value of the ornaments has specific purposes related to Betawi?s cultural and social customs. Therefore, the application needs to consider more about the purpose of the symbol of the ornament.